2012
DOI: 10.1038/cdd.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic-induced cleavage shifts HuR from being a promoter of survival to an activator of caspase-mediated apoptosis

Abstract: Little is known about the cellular mechanisms modulating the shift in balance from a state of survival to cell death by caspasemediated apoptosis in response to a lethal stress. Here we show that the RNA-binding protein HuR has an important function in mediating this switch. During caspase-mediated apoptosis, HuR is cleaved to generate two cleavage products (CPs). Our data demonstrate that the cleavage of HuR switches its function from being a prosurvival factor under normal conditions to becoming a promoter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…11 The RRM3-containing cleavage product may acquire new functions in triggering apoptosis as it selectively binds to and stabilizes caspase-9 mRNA in an ARE-dependent manner. 12 The NMR titration data herein reported and earlier findings with HuB, 59 demonstrate that isolated RRM3 can bind to AREs, although previous studies suggested a negligible role of HuR RRM3 ¡ as part of HuR FL ¡ in AREs recognition. 34,[44][45][46] Isolated RRM3 is in a monomer/dimer exchange on a time scale unfavorable for NMR observation of the residues at the dimerization site, notably those in the W261-T271 region at the C-end of helix a 1 .…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…11 The RRM3-containing cleavage product may acquire new functions in triggering apoptosis as it selectively binds to and stabilizes caspase-9 mRNA in an ARE-dependent manner. 12 The NMR titration data herein reported and earlier findings with HuB, 59 demonstrate that isolated RRM3 can bind to AREs, although previous studies suggested a negligible role of HuR RRM3 ¡ as part of HuR FL ¡ in AREs recognition. 34,[44][45][46] Isolated RRM3 is in a monomer/dimer exchange on a time scale unfavorable for NMR observation of the residues at the dimerization site, notably those in the W261-T271 region at the C-end of helix a 1 .…”
Section: Discussionmentioning
confidence: 45%
“…In this sense, our data is consistent with RRM3 being easily removed from the HuR core by a caspasemediated cleavage, which is a regulatory event that enhances the apoptotic response. 11,12 Solution structure of HuR RRM3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 In response to lethal stress, caspase-3 and -7 cleave HuR to release interacting apoptosome effectors and amplify proapoptotic loops. 59,60 Our current findings suggest for the first time that these differences may be because of the differential need for HuR in apoptosis versus necrosis, which includes several modes of programmed cell death (e.g. necroptosis, oxytosis, parthanatos).…”
Section: Discussionmentioning
confidence: 72%
“…During caspase-mediated apoptosis, HuR switches its function from pro-survival to pro-apoptotic [203]. Caspases can mediate cleavage of HuR under different situations [204].…”
Section: Suppression Of the Heat Shock Response In Agerelated Degenermentioning
confidence: 99%